Factors related to stigma among patients with cervical cancer having chemotherapy after surgery in China: A cross-sectional study - Wang, Fanglin; Hengudomsub, Pornpat; Chantamit-o-pas, Chutima (Belitung Raya Publisher - Belitung Raya Foundation, 2025)
Background: Stigma is a significant issue among patients with cervical cancer undergoing postoperative chemotherapy, yet the factors contributing to stigma are not well understood. While research has explored the relationships between self-efficacy, illness perception, self-esteem, social support, and stigma, fewer studies have focused on Chinese patients, and even fewer have specifically examined stigma within this population. Objective: This study aimed to describe stigma and assess its association with self-efficacy, self-esteem, illness perception, and social support in postoperative chemotherapy patients diagnosed with cervical cancer. Methods: A total of 132 participants were recruited from the gynecology department of Wenzhou Medical University’s First Affiliated Hospital using a random sampling technique. Data were collected between December 2023 and April 2024 using validated instruments. Descriptive statistics and Spearman’s rank correlation were used for data analysis. Results: The average stigma score was 76.3 (SD = 10.84), indicating a high level of stigma. Self-efficacy, self-esteem, illness perception, and social support were negatively correlated with stigma (r = -0.085, r = -0.158, r = -0.254, r = -0.238, all p <0.05). Conclusion: All participants experienced significant stigma. The negative correlations found between stigma and self-efficacy, self-esteem, illness perception, and social support offer a theoretical basis for developing nursing interventions to reduce stigma in these patients.